PERBANDINGAN NILAI TAHANAN PENTANAHAN PADA AREA REKLAMASI PANTAI (CITRALAND) - Mukmin, Mirwan; Kali, Agustinus; Mukhlis, Baso (MEKTRIK)
Abstract Grounding system is a system that connects conductive connection systems, equipment and installations bodies with earth / ground so as to secure the human from electric shock, and secure the installation components from the dangers of the voltage / current abnormal. Therefore, the earthing system becomes an essential part of the power system. The study was conducted to measure and compare the value of grounding resistance on an area of reclaimed and non-reclaimed beach in a residential area of â€‹â€‹Citra Land, PT. Ciputra Surya, JO. that will facilitate the future design of earthing systems. Types of electrodes used in the measurement of the electrode is a single rod with a diameter of 0.15 m and a length of 1.4 meters, which were planted at a depth of 0.25 / 0.5 / 0.75 / 1 meter from the ground, measuring instruments used are analog Earth Resistance Tester 3235. Grounding resistance value measurement performed ten times in order to get the value can be averaged so get earth resistance value desired. Value of the grounding resistance measurement results reclaimed land amounted to 3.03 Î©, while the non-reclaimed land by 5 Î©. For the value of soil resistivity on the reclaimed land of 0.455 Î©, while for non-reclaimed land of 1.481 Î©. Â Keywords: Reclamation, earthing, electrode and soil resistivity.